PHOTOCHEMICAL ACTIVATION OF AIR POLLUTANTS, RELATED TO THE PRESERVATION OF CULTURAL HERITAGE - Ivan Juranić (Journal of Engineering & Processing Management, 2011)
It is well known that the exposition to air and weather markedly enhances derogation of all artifacts. In this report, the contribution of light (particularly sunlight) to marked speed-up of the oxidation and other changes by exposition to atmosphere will be analyzed. Five major mechanisms of the effect of insolation can be identified: 1. First is a trivial one – the heating effect which enhances all chemical processes. 2. Photoexcitation of material from which the item is made, turning it more reactive toward air oxygen (and to other present substances). 3. Sensitization of oxygen by excitation to singlet state in which it is extremely reactive, and can react even with inert materials. 4. Photochemical transformation of volatile organic compounds (VOC), primarily aldehydes and ketones, that can with oxygen yield organic acids and hydroperoxides which definitely harm majority of materials. 5. In contact of oxygen and another material, upon the absorption of light quanta, a charge transfer process can occur, giving yield to pairs of ion-radicals, which further can be transformed in various reactive products.
Keywords: Photooxygenation; Chemical mechanism; Air pollutants